Effect of propolis extract on the skin healing process: a literature review - Pereira, Thercyo Ariell Costa (2022)
Propolis is a resinous substance obtained by bees from the buds, leaves, bark and exudates of many trees and plants. Propolis and its extracts have long been used for the prevention and treatment of a variety of infections and diseases due to their antimicrobial, anti-inflammatory, antiparasitic, antioxidant and healing activities. Thus, taking into account the numerous therapeutic properties and biological applications of propolis extract, this study aims to address, through a literature review, the benefits of using propolis extract in the treatment of injuries and wound healing in the skin. Data were obtained through a search in the Pubmed databases and in the Virtual Health Library covering the period 2017 to 2021, in Portuguese, English and Spanish, using the following descriptors: "propolis extract" and "healing" and “propolis extract” and “healing”. All articles were selected by reading the title and abstract that analyzed the role of the propolis extract in wound healing in the period 2017-2021. The 14 articles selected for the study showed, through clinical studies in humans, experimental "in vitro" and in animals, the effectiveness of propolis extract in the treatment of wounds, acting as a natural healing and antimicrobial agent, whose properties depend directly on the form and place of extraction and concentration of the product. In this perspective, the propolis extract has a promising application in the treatment of skin lesions.